Effective Information Technology Governance Mechanisms: An Australian Study - Syaiful Ali (Gadjah Mada International Journal of Business, 2006)
Growing importance of information technology (IT), as a strategic factor for organizations in achieving their objectives, have raised the concern of organizations in establishing and implementing effective IT governance. This study seeks to empirically examine the individual IT governance mechanisms that influence the overall effectiveness of IT governance. The data were obtained by using web based survey from 176 members of ISACA (Information Systems and Audit Control Association) Australia. This study examines the influences of six proposed IT governance mechanisms on the overall effectiveness of IT governance. Using Factor Analysis and Multiple Regression techniques, the current study finds significant positive relationships between the overall level of effective IT governance and the following four IT governance mechanisms: the existence of ethics/ culture of compliance in IT, corporate communication systems, an IT strategy committee, and the involvement of senior management in IT.